Pembuatan Aplikasi Penjadwalan dan Reservasi untuk Penggunaan Private Cloud Computing - Halim, Albert; Palit, Henry Novianus; Noertjahyana, Agustinus (Jurnal Infra, 2015)
Cloud computing is a new technology that is being hotly discussed by experts in information technology. Cloud computing technology is here to address the challenge of more efficient computing technologies. So an idea has come about to build a cloud system in the Petra Christian Universityâs computer laboratory. However implementing the cloud could interfere with the use of existing lab. The application aims to help the user manage the cloud system to run according to the desired schedule.The application development involved evaluation on the scheduling system, enhancement on the filter scheduler to accommodate a time schedule, and creation of the web-based user interface to manage the time schedule (in the form of a calendar).The application can restrict the OpenStacks instance deployment only on the time schedule allowed by the system administrator. In addition, the system scheduler has negligible latency (overhead), so that it will not affect the system schedulerâs performance.